Strong volcanic-induced climatic shocks on historical Moselle wine production - F. C. Ljungqvist; F. C. Ljungqvist; F. C. Ljungqvist; B. Christiansen; L. Schneider; L. Schneider; P. Thejll (Climate of the Past)
In central and southern Europe, grapevine is a climate-sensitive agricultural product of great economic importance, both in historical times and today. We systematically investigated the climatic impact, focusing on volcanic-forced abrupt cooling, on two long annual records of wine production quantity (spanning 1444–1786) from the Moselle Valley in present-day Luxembourg, close to the northern limit of viticulture in Europe. We present a consistent picture of the impact of volcanic eruptions on wine production through climate. To this end, we applied superposed epoch analysis – an appropriate method for detecting episodic signals in non-stationary time series – in combination with a bootstrap procedure to estimate the statistical significance. We also assessed the long-term relationship between different annual and seasonal climate parameters and wine production in the Moselle Valley. Robust and highly significant wine production declines occurred in the years immediately following major volcanic events. Warmer and, to a lesser extent, drier climate conditions had a moderately strong, but persistent, positive effect on wine production. We also find a volcanic cooling signature in spring and summer in temperature reconstructions. However, the detected volcanic signature in the Moselle Valley wine production is considerably stronger than the one found for central Europe in tree-ring-based reconstructions and is instead more akin to the strong volcanic signature present in Fennoscandian tree-ring series. On the basis of our findings, we encourage further compilation, publication, and analyses of additional wine production series containing unique biological and climatic information.